2012
DOI: 10.1155/2012/907162
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Mechanisms Underlying the Aged Garlic Extract- and S-Allylcysteine-Induced Protection

Abstract: Aged garlic extract (AGE) is an odorless garlic preparation containing S-allylcysteine (SAC) as its most abundant compound. A large number of studies have demonstrated the antioxidant activity of AGE and SAC in both in vivo—in diverse experimental animal models associated to oxidative stress—and in vitro conditions—using several methods to scavenge reactive oxygen species or to induce oxidative damage. Derived from these experiments, the protective effects of AGE and SAC have been associated with the preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(214 citation statements)
references
References 114 publications
(147 reference statements)
8
192
1
13
Order By: Relevance
“…Several experimental and clinical investigations have reported many favourable effects of garlic and its preparations. Such effects include: (i) reduction of risk factors for cardiovascular diseases, (ii) reduction of cancer risk, (iii) antioxidant effect, (iv) antimicrobial effect against bacteria, viruses, fungi and parasites, (v) detoxification of foreign compounds and hepatoprotection, and (vi) decrease in platelet aggregation and atherosclerotic plaques (Colín-González et al 2012;Bayan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and clinical investigations have reported many favourable effects of garlic and its preparations. Such effects include: (i) reduction of risk factors for cardiovascular diseases, (ii) reduction of cancer risk, (iii) antioxidant effect, (iv) antimicrobial effect against bacteria, viruses, fungi and parasites, (v) detoxification of foreign compounds and hepatoprotection, and (vi) decrease in platelet aggregation and atherosclerotic plaques (Colín-González et al 2012;Bayan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Preventive strategies that treat obesity through exercise with or without nutritional supplementation can have important effects on is important factor in obesity [8]. Aged garlic extract (AGE) is well-documented alternative source of garlic that is odorless and rich in antioxidants [9]. Moreover, it has been reported that AGE may play a role in the mitigation of cardiovascular disease [10,11], inflammation [12], hypertension [13], and cancer risk [14].…”
Section: Introduction 9)mentioning
confidence: 99%
“…[ [29][30][31] Animal studies had also reported anti hyperlipidemic effects of garlic extract. [32,33] Interventional studies have similarly shown anti hyperlipidemic effects of total plasma lipids in humans.…”
Section: European Journal Of Pharmaceutical and Medical Researchmentioning
confidence: 99%